Corporate governance and strategic information disclosure in Malaysian listed banks : panel data analysis - Htay, Sheila Nu Nu; Aung, Zaw Min; Ab. Rashid, Hafiz-Majdi; Adnan, Muhammad Akhyar (2011)
Corporate governance issue has attracted the researchers, especially the Malaysian researchers due to the 1997-1998 economic crises. Furthermore, it is undeniable that the banking sector is the heart of the economy in any country since it is the main source in mobilizing the monetary system. Thus, this study investigates the impact of corporate governance on strategic information disclosure of Malaysian listed banks by using a panel data analysis.